ANALYSIS OF LANGUAGE ERRORS IN PHONOLOGY AND MORPHOLOGY IN BOY CANDRA'S TWITTER TWEETS - Anggi Andini; Ferani Siti Nurhanifah; Indri Apriliani Jatnika; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Social media, one of which is Twitter, is a means to communicate that is very close to the social life of young people, but the use of good Indonesian is decreasing, so it often causes deviations in using Indonesian, both in writing and verbally. The purpose of this study is to describe the analysis of language errors in the field of phonology and morphology contained in Boy Candra's Twitter tweets for two months, namely October-November 2023, in which there are language errors. This research uses descriptive-qualitative methods with research techniques, listen and record, which is then presented through the analysis table. Found phonological and morphological errors include; First, the phonology field has 7 phoneme reduction errors, 1 punctuation error and 1 foreign language usage error. Second, in the field of morphology there are 3 additions to prefix affixes and 1 error of combined word elements that should be written separately.